Biogeography and co-occurrence of 16 planktonic species of Keratella Bory de St. Vincent, 1822 (Rotifera, Ploima, Brachionidae) in lakes and reservoirs of the United States - Tausz, Claudia E.; Beaver, John R.; Renicker, Thomas R.; Klepach, Julia A.; Pollard, Amina I.; Mitchell, Richard M. (Zootaxa, 2019)
We report current distributions of 16 species of Keratella Bory de St. Vincent, 1822 within lakes and reservoirs of the U.S. Specimens were identified from 988 lakes and reservoirs during spring and summer 2012 as part of the U.S. Environmental Protection Agency’s National Lakes Assessment (NLA). We performed a co-occurrence analysis to determine correlations between species-pair occurrences and a niche-centroid analysis to predict optimal water quality conditions for each species. While a high degree of overlap in geographic range was observed among the species, distribution maps showed that K. quadrata was largely confined to more northern latitudes and K. americana was confined primarily to the eastern U.S. Other common species were either ubiquitously or sparsely distributed across ecoregions, suggesting that their distribution may be more related to inter-species competition or local water quality parameters. This study expands the limited pool of knowledge on rotifer biogeography within the U.S.